isKARDABA business plan.
Executive summary-As one of its major crops in its terrains, Bingawan, an agricultural municipality, has adpated the abundance of bananas and the products derived from its as a means of promoting the town's name nationally. Cardava (Musa balbisiana) banana, also known as saba is one of the species of banana that is mostly abundant in the municipality of Bingawan. It has the highest content among all other banana plants due to its deep roots which enables it to absorb more nutrient from the soil. almost every part of saba banana can be economically utilized and its fruit can be eaten ripe or cooked and can also be processed to a wide variety of products. The GUINTAPAGIN Agrarian Reform community is one of the most progressive cooperatives in Bingawan. It was organized in October 2002 and its office is located in Brgy. Tapacon, Bingawan, Iloilo. On October 2006, the Department of Trade and Industry (DTI), together with the Local Government Unit (LGU) of Bingawan, initiated trinings on food processing specifically on banana homemade delicacies namely: banana chips, muffins, fries, syrup and polvoron with real banana bits. After the training, the GUINTAPAGIN ARC was able to generate income from producing these homemade banana delicacies. With the vision of helping Bingawan to mark its name in the banana industry, isKARDABA was created. isKARDABA is a partnership between a group of all-female students of the University of the Philippines Visayas and the members of the GUINTAPAGIN agrarian Reform Community. The business was established to improve the cooperative's existing products and to develop new ones which can provide more livelihood opportunities for the members of the cooperative. One of the Plans of isKARDABA is to be able to produce banana flour which will be initially used as a raw material in the creation of the products of GUINTAPAGIN ARC. Having a very fine texture, the banana flour is perfect for making polvoron and banana muffins. isKARDABA goes by the tagline "Produktong Masusta siya, Presyong Pang-masa" The target market of iskardaba is identified by three segmentations: geographical, demographics and psychographics. The products will be introduced to a wider market in the city of Iloilo which includes the city terminals (i.e. Tagbak Terminal, Molo Terminal, Ungka Terminal), seaports (i.e. Iloilo-Guimaras, Port, Parola) and malls (i.e. SM City Iloilo, Robinson's Place Iloilo). The main competitive advantage of isKardaba over its competitors are its healthy banana products with a twist and theproducts are to be sold at a more inexpensive price compared to the prices of its competitors. The over-all strategy of the isKARDABA is mainly focused on the methods on how to reach the vision of the company. The company will also offer future products such as banana cookies, banana muffins made from banana flour and banana vinegar from banana peelings. To promote the products, isKARDABA will utilize social networking sites such as Facebook, Tweeter and Instagram, join trade fairs, distribute posters and brochures, and make use of the media strategy, and the most traditional, the "word of mouth" strategy. GUITAPGIN ARC is one of the beneficiaries of the Department of Science and Technology's (DOST Technology Based Incubation Center Project and received equipments such as stainless working tables and industrial burner stove tops that are necessary for the production of banana-products. The Department of Trade and Industry (DTI) also granted the cooperative equipment such as food dryer, mechanical slicer and refrigerator. Because of this, the start-up costs of isKARDABA will only include expenses for additional equipment, ingredients, transportation and allowance for employee's in the first month of operation. The start-up cost of isKARDABA will total to only P20,600. During the first year of operation, isKARDABA will have a revenue of p647,650 with a net income of p152,853.90. With a five-year projection, the company can have a net income of up to P216,121.63. isKARDABA also contributes to the welfare of its local community in a number of ways. One is for the livelihood of the members of the GUINTAPAGIN ARC. The cooperative provides a source of income to more than a hundred citizens from the member barangays. isKARDABA also helps in the waste reduction. The team aims to turn every part of the banana plant, even the peels, to a product and waste as little of the ingredients as possible. The banana peels can actually be used to make banana vinegar and the Department of Science and Technology is currently conducting a research regarding this. Banana peels can also be used as a fertilizer and for vermiculture. Since the business is offering banana-based products, there is no doubt about the health benefits that the isKARDABA product can give.